Some New Identities on the Bernoulli and Euler Numbers - Dae San Kim; Taekyun Kim; Sang-Hun Lee; D. V. Dolgy; Seog-Hoon Rim (Discrete Dynamics in Nature and Society)
We give some new identities on the Bernoulli and Euler numbers by using the bosonic p-adic integral on Zp and reflection symmetric properties of Bernoulli and Euler polynomials.